ANALISIS PERCEPATAN WAKTU PROYEK DENGAN METODE CRASHING DAN LAST PLANNER SYSTEM (LPS): STUDI KASUS PROYEK PEMBANGUNAN GEDUNG FASILITAS PENGEMBANGAN PRODUK SKALA PILOT (GEDUNG NO.34) - Maharani, Tiara; Herzanita, Ayu (Construction and Material Journal, 2025)
The problem of delay remains a major challenge in the construction world. During the implementation of construction projects, delays are often caused by obstacles or unplanned problems. Delays lead to the duration of project execution not as planned in the work contract. Many ways are done to overcome project schedule delays such as the crashing time acceleration method and the Last Planner System (LPS). The crashing method is carried out by accelerating the duration of project completion by carrying out three systems, namely increasing manpower, changing work time (shifts) and adding work time (overtime). Meanwhile, the LPS is a planning system based on collaboration, integrated commitment between works by involving people who are directly responsible and understand the work in a production unit. This study aims to analyze the acceleration of time with the Crashing method and with the LPS then compare the effectiveness of time acceleration between the two methods. Case study from the Pilot Scale Product Development Facility Building (Building No.34). The problem is what level of efficiency in both methods of time acceleration will be analyzed. The implementation of crashing with alternatives shift work reduces the project duration by 22 days, whereas the simulation of the LPS increases the actual weight compared to planning. The difference between the two method is that the crashing method is applied after delays occur, while the LPS accelerates work and increases productivity by utilizing continuous team collaboration.